2022
DOI: 10.1039/d2ra02005j
|View full text |Cite
|
Sign up to set email alerts
|

Advances with metal oxide-based nanoparticles as MDR metastatic breast cancer therapeutics and diagnostics

Abstract: Biomarker targeted therapy approaches for TNBC using metal oxide-based NPs are highly effective and promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 201 publications
0
9
0
Order By: Relevance
“…Nanocarriers, including liposomes, , metal/metal oxide nanoparticles, polymer nanoparticles, and nanosized metal–organic frameworks, are usually relatively large, with diameters spanning tens of nanometers. As a result, nanocarriers are typically unable to cross membranes, and they are generally internalized into cells by endocytic uptake mechanisms. , Notably, this is the case for other reported PCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Nanocarriers, including liposomes, , metal/metal oxide nanoparticles, polymer nanoparticles, and nanosized metal–organic frameworks, are usually relatively large, with diameters spanning tens of nanometers. As a result, nanocarriers are typically unable to cross membranes, and they are generally internalized into cells by endocytic uptake mechanisms. , Notably, this is the case for other reported PCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several research approaches that combine the effects of metal oxides (MO) with targeting the acidic TME were developed in order to obtain enhanced antitumor efficacy. The interest on MO nanoparticles is due to their pro-apoptotic activity; inhibition of tumor cell growth and metastasis, and ROS production [ 231 , 232 ]. A characteristic example of an MO is cerium oxide nanoparticles (nanoceria).…”
Section: Nanomedicines For Targeting Tme: Application Of Natural and ...mentioning
confidence: 99%
“…Chemotherapy resistance is often the main cause of chemotherapy failure, especially in MBC and TNBC, and it even accounts for approximately 90% of treatment failures (Nedeljkovic and Damjanovic, 2019). More and more studies have revealed that the development of resistance to MBC chemotherapy is complex and is based on several factors, including the interaction of TME, drug efflux, cancer stem cells, and bulk tumor cells, while changes in multiple signaling pathways control these interactions (Mao et al, 2013;Boelens et al, 2014;Luo et al, 2020;Gao et al, 2021;Subhan, 2022). At present, in-depth study of chemotherapy drugs has also found their adverse mechanism of action.…”
Section: Current Treatment Strategies and Challenges Of Bclmmentioning
confidence: 99%